2004
DOI: 10.1902/jop.2004.75.2.327
|View full text |Cite
|
Sign up to set email alerts
|

Success and Failure Rates of 9 mm or Shorter Implants in the Replacement of Missing Maxillary Molars When Restored with Individual Crowns: Preliminary Results 0 to 84 Months in Function. A Retrospective Study

Abstract: These findings suggest that non-countersunk implants of 7 to 9 mm in length may be successfully restored with single crowns in the maxillary molar region.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(74 citation statements)
references
References 10 publications
2
62
1
8
Order By: Relevance
“…Similarly, Papavasiliou et al (10) demonstrated that oblique forces increased the stress concentration in the implant and bone. These results are also in accordance with the literature that describes the influence of increase in crown height on the transference of occlusal forces (9,11,13,15,(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similarly, Papavasiliou et al (10) demonstrated that oblique forces increased the stress concentration in the implant and bone. These results are also in accordance with the literature that describes the influence of increase in crown height on the transference of occlusal forces (9,11,13,15,(18)(19)(20)(21)(22)(23)(24).…”
Section: Discussionsupporting
confidence: 92%
“…A biomechanical test examining crown height (10, 12 and 14 mm) demonstrated displacement of the highest crown only under oblique loading (14). In addition, it has been found that unfavorable crown-to-root ratio associated with parafunctional habits could lead to failure and dysfunction (15).…”
Section: Introductionmentioning
confidence: 99%
“…Estudos de acompanhamento a longo prazo com o uso de implantes curtos têm demonstrado bons resultados, mesmo com reabilitações individualizadas (Lindh et al, 1998;Fugazzotto et al, 2004), tal como …”
Section: Uso De Implantes Com Comprimento Reduzidounclassified
“…Tais resultados contradizem o conceito que coroas com dimensão vertical aumentadas são contraindicadas para reabilitação de áreas posteriores, tal como dito por Rangert et al, 1997e Glantz e Nilner (2000. Ao mesmo tempo, o estudo de Blanes et al (2007) corrobora com os achados de Celletti et al (1995), Lindquist et al (1996) Henry et al (1996), Scheller et al (1998), Mericske-Stern et al (2001), Fugazzotto et al (2004), Glauser et al (2005) e Renouard e Nisand (2005).…”
Section: Proporção Coroa/implanteunclassified
“…No caso de implante hexágono externo, deve ser instalado em nível ósseo, podendo haver reabsorção óssea ao redor do implante no nível da interface implante/prótese, e então reduzindo em torno de 2mm o contato entre osso e implante, desse modo o implante curto ficaria com menor contato ossoimplante, o que não é visto em implantes de conexão Cone Morse, de instalação infra óssea (FUGAZZOTTO et al,2004 CHOU et al, 2010).…”
Section: Implantes Estreitosunclassified